URGENSI PEMBERIAN GANTI KERUGIAN TERHADAP ANAK YANG MENJADI KORBAN KEKERASAN SEKSUAL - Tiana Elvijani (2022)
In cases of sexual violence against children, the problem that often occurs is regarding legal protection for victims which is only limited to punishing the perpetrators. In fact, to restore the victim's condition, more protection is needed than that, one of which is compensation for the victim. The problems studied are: (1). What is the urgency of giving compensation to children who are victims of sexual violence? (2). What efforts can be made in optimizing the implementation of compensation for child victims? This study aims to determine the background of the urgency of providing compensation to children victims of sexual violence and the efforts made to optimize the implementation of compensation. This research is a normative legal research that uses a statutory approach and a conceptual approach. The results of the research on the background of child victims of sexual violence need to get compensation, namely: First, the rights of child victims to obtain compensation for what happened to them. Second, the physical, psychological, social and economic impacts experienced by children will affect their survival. Third, the weak position of children as victims in criminal justice. Fourth, the deterrent effect on the perpetrator by imposing an obligation to pay a certain amount of money, so that the perpetrator does not repeat his actions again. Efforts can be made to optimize the implementation of compensation by establishing a special unit for cases of sexual violence in the Police, facilitating application requirements, supervising the assets of perpetrators, conducting training for law enforcement officers and establishing a victim aid fund. Keywords: compensation, restitution, compensation, sexual violence against children